Injectable gellan-gum/hydroxyapatite-based bilayered hydrogel composites for osteochondral tissue regeneration. (September 2018) - Pereira, D.R.; Canadas, R.F.; Silva-Correia, J.; da Silva Morais, A.; Oliveira, M.B.; Dias, I.R.; Mano, J.F.; Marques, A.P.; Reis, R.L.; Oliveira, J.M.
Graphical abstract: Schematic representation of the experimental design. Eight different bilayered hydrogel composites (BHC) were fabricated and characterised for physico-chemical and mechanical properties varying both cartilage-like and bone-like layers. Afterwards, four of those BHC were selected for further in-vitro testing to screen possible toxicity and viability/proliferation of OC-derived cells. Therefore, one BHC (LAGG/LAGG-HAp 20%) was chosen for in-vivo citocompatibility testing by subcutaneous implantation and further functional performance in an orthotopic knee model in rabbit. Abstract: Multilayer systems capable of simultaneous dual tissue formation are crucial for regeneration of the osteochondral (OC) unit. Despite the tremendous effort in the field there is still no widely accepted system that stands out in terms of superior OC regeneration. Herein, we developed bilayered hydrogel composites (BHC) combining two structurally stratified layers fabricated from naturally derived and synthetic polymers, gellan-gum (GG) and hydroxyapatite (HAp), respectively. Two formulations were made from either low acyl GG (LAGG) alone or in combination with high acyl GG (HAGG) for the cartilage-like layer. Four bone-like layers were made of LAGG incorporating different ratios of hydroxyapatite (HAp). BHC were assembled in one single construct resulting in eight distinct bilayered constructs. Architectural observations by stereomicroscope and micro-CT (μ-CT) demonstrated a connected stratified structure with good ceramic dispersion within the bone-like layer. Swelling and degradation tests as well mechanical analyse showed a stable viscoelastic construct under dynamic forces. In-vitro studies by encapsulating rabbit's chondrocytes and osteoblasts in the respective layers showed the cytocompatibility of the BHC. Further studies comprising subcutaneous implantation in mice displayed a weak immune response after four weeks. OC orthotopic defects in the rabbit's knee were created and injected with the acellular BHC. OC tissue was regenerated four weeks after implantation as confirmed by cartilaginous and bony tissue formation assessed by histologic staining and μ-CT analysis. The successful fabrication of injectable BHC and their in-vitro and in-vivo performance may be seen as advanced engineered platforms to treat the challenging OC defects.